Chlorophyll Response in Ipomoea reptans Leaves to Liquid Organic Fertilizer Application from Vegetable Waste - Mega Nofitri Ikhwan; Prapti Sedijani; Rubiyatna Sakaroni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Modern agricultural practices that use synthetic inorganic fertilizers excessively and uncontrolled can disrupt the soil’s ecological balance, reduce microbial activity, and disrupt plant physiological processes, so that the development of alternative, environmentally friendly fertilizers is needed. This study aimed to evaluate the physiological response of Ipomoea reptans to the application of LOF derived from vegetable waste, using leaf chlorophyll content and vegetative growth parameters as indicators. The experiment was conducted using a Completely Randomized Design (CRD) with treatments consisting of combinations of NPK fertilizer and LOF at different concentrations. The observed parameters included the number of leaves, leaf area, and chlorophyll content, and the data were analyzed using One-Way ANOVA followed by Tukey’s test and Pearson correlation analysis. The results showed that the application vegetable-waste LOF tended to enhance the vegetative growth of Ipomoea reptans, with the highest number of leaves and leaf area observed in treatment N0P3 (0 g NPK + 60 ml LOF). However, statistical analysis indicated that most treatments did not differ significantly at the 5% significance level. Chlorophyll content also did not differ significantly among treatments, although the highest value was recorded in treatment N0P2 (40 ml LOF without NPK). Pearson correlation analysis revealed a very weak and non-significant relationship between leaf number and chlorophyll content (r = −0.019; p = 0.916; n = 32) and between leaf area and chlorophyll content (r = −0.045; p = 0.807; n = 32). Based on data, there is a tendency to increase vegetative growth with vegetable waste-based LOF, although statistically there is no significant difference. These findings indicate that vegetable waste-based LOF has the potential to be developed as an environmentally friendly alternative fertilizer to support sustainable cultivation and improve understanding of plant physiological responses during vegetative growth.